Design and Measurement of Performance Parameters of Micro strip Patch Antenna used for Wi - Max and C-Band Applications - D, Pavitra; G. Nayak, Subramanya (International Journal of Engineering and Technology, 2018)
In this paper the design of Multi-Band patch antenna is discussed. This Multi-Band operation is achieved by cutting few slots on the radiating patch. Co-axial feeding technique is employed in the design and FR4 is taken as the dielectric substrate. The simulation results along with different antenna parameters such as Return loss, VSWR are plotted. The designed antenna resonates at 3.8GHz, 6.1GHz, 7.1GHz, 8.6GHz and 9.1GHz frequencies with increased bandwidth and this antenna can be used in WI-MAX and C band applications.Â Â Â